At Westonci.ca, we connect you with experts who provide detailed answers to your most pressing questions. Start exploring now! Discover comprehensive answers to your questions from knowledgeable professionals on our user-friendly platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To find the point-slope form of the equation of the line passing through the points [tex]\((1,0)\)[/tex] and [tex]\((6,-3)\)[/tex], we must follow a series of steps. Let's go through them:
1. Identify the coordinates:
- Point 1: [tex]\((x_1, y_1) = (1, 0)\)[/tex]
- Point 2: [tex]\((x_2, y_2) = (6, -3)\)[/tex]
2. Calculate the slope [tex]\(m\)[/tex]:
The slope [tex]\(m\)[/tex] between two points [tex]\((x_1, y_1)\)[/tex] and [tex]\((x_2, y_2)\)[/tex] is given by the formula:
[tex]\[ m = \frac{y_2 - y_1}{x_2 - x_1} \][/tex]
Plugging in the coordinates:
[tex]\[ m = \frac{-3 - 0}{6 - 1} = \frac{-3}{5} = -0.6 \][/tex]
3. Use the point-slope form of the equation:
The point-slope form of a line is given by:
[tex]\[ y - y_1 = m (x - x_1) \][/tex]
We can use either point to write the equation. Let's use the point [tex]\((6, -3)\)[/tex]:
[tex]\[ y - (-3) = m (x - 6) \][/tex]
4. Substitute the slope [tex]\(m\)[/tex] in the equation:
We already calculated that [tex]\(m = -0.6\)[/tex]. Using this value:
[tex]\[ y - (-3) = -0.6 (x - 6) \][/tex]
So, the point-slope equation of the line is:
[tex]\[ y - (-3) = -0.6 (x - 6) \][/tex]
or
[tex]\[ y + 3 = -0.6 (x - 6) \][/tex]
Thus, the completed point-slope equation is:
[tex]\[ y - (-3) = -0.6 (x - 6) \][/tex]
1. Identify the coordinates:
- Point 1: [tex]\((x_1, y_1) = (1, 0)\)[/tex]
- Point 2: [tex]\((x_2, y_2) = (6, -3)\)[/tex]
2. Calculate the slope [tex]\(m\)[/tex]:
The slope [tex]\(m\)[/tex] between two points [tex]\((x_1, y_1)\)[/tex] and [tex]\((x_2, y_2)\)[/tex] is given by the formula:
[tex]\[ m = \frac{y_2 - y_1}{x_2 - x_1} \][/tex]
Plugging in the coordinates:
[tex]\[ m = \frac{-3 - 0}{6 - 1} = \frac{-3}{5} = -0.6 \][/tex]
3. Use the point-slope form of the equation:
The point-slope form of a line is given by:
[tex]\[ y - y_1 = m (x - x_1) \][/tex]
We can use either point to write the equation. Let's use the point [tex]\((6, -3)\)[/tex]:
[tex]\[ y - (-3) = m (x - 6) \][/tex]
4. Substitute the slope [tex]\(m\)[/tex] in the equation:
We already calculated that [tex]\(m = -0.6\)[/tex]. Using this value:
[tex]\[ y - (-3) = -0.6 (x - 6) \][/tex]
So, the point-slope equation of the line is:
[tex]\[ y - (-3) = -0.6 (x - 6) \][/tex]
or
[tex]\[ y + 3 = -0.6 (x - 6) \][/tex]
Thus, the completed point-slope equation is:
[tex]\[ y - (-3) = -0.6 (x - 6) \][/tex]
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.